OPTIMIZATION OF ONLINE EXAMINATION DEVELOPMENT ON NEW STUDENTS ADMISSION OF POLYTECHNIC FURNITURE AND WOOD PROCESSING INDUSTRY WITH ECONOMIC AND TECHNOLOGICAL FEASIBILITY ANALYSIS - Ulfia, Yessi Nasia; Kristianto, Fesa Putra Kristianto; Shoffiyati, Peni; Rosada, Magfur (Jurnal Bisnis dan Keuangan, 2023)
The admission of new students at the Polytechnic of Furniture and Wood Processing Industry (Polifurneka) has a significant impact on the quality of education, One of which is the level of competence of the new students who are accepted. Therefore, it is necessary to optimize the development of a new student admission selection system using the CAT (Computer Assisted Test) online examination system to produce competent students. There are three online exam system options that can be implemented at the Furniture and Wood Processing Industry Polytechnic, namely the online exam system by making your own, an online exam system provided by PT. X and online exam system of premium upgrade google form. Therefore these three options must be analyzed economically and technologically. Based on the economic and technological feasibility analysis, an online exam is chosen that is self-exam. In the economic feasibility of the online exam made by itself, it provides a Payback Ratio (PP) value of 0.12 years, Net Present Value (NPV) of Rp. 446.088.408,-, Return On Investment (ROI) of 13,229%, and from the results of technology analysis, the online exam made by yourself is considered feasible because there is an additional listening question feature and storage capacity of up to 900,000 register per month.